Effects of warm-up and precooling on endurance performance in the heat - Ückert, S.; Joch, W. (British Journal of Sports Medicine, 2007)
Objective: To examine the effects of different thermoregulatory preparation procedures (warm-up (WU), precooling (PC), control (C)) on endurance performance in the heat.